Pectin extraction from kepok banana peel waste (Musa acuminata balbisiana) based on green chemistry as a natural preservative - Ramandha, Muhammad Eka Putra; Isasih, Widani Darma; Ekaningsih, Astrid (Pascasarjana Universitas Negeri Medan, 2024)
The aims of this research are (1) to extract pectin from kepok banana peels with an environmentally friendly solvent, namely tamarind and (2) to use pectin as a fruit and vegetable preservative. The research methods used were (1) extraction (2) Compound identification test using FTIR (3) Test the effectiveness of pectin's ability to preserve fruit and vegetables. The results of the research showed that the percent yield obtained was 26% and the results of compound identification showed that there were wavelengths corresponding to pectin compounds. The results of testing the effectiveness of pectin's ability to preserve the average result showed that pectin can increase the rotting time of fruit and vegetables. The conclusion from the results of this research is that tamarind can be used as a natural solvent in extracting pectin from kepok banana peels and pectin can be used as a natural preservative for fruit and vegetables.